The Granta book of the African short story - Habila, Helon 1967- (London Granta Publications, 2012)
The Granta Book of the African Short Story introduces a group of African writers described by its editor, Helon Habila, as 'the post-nationalist generation'. Introducing a diverse and dazzling collection from all over the continent - from Morocco to Zimbabwe, Uganda to Kenya - Habila has focused on younger, newer writers, interspersed with some of their older, more established peers, to give a fascinating picture of a new and more liberated Africa. Disdaining the narrowly nationalist and political preoccupations of previous generations, these writers are characterized by their engagement with the wider world and the opportunities offered by the internet, the end of apartheid, the end of civil wars and dictatorships, and the possibilities of free movement around the world. Many of them live outside Africa. Their work is inspired by travel and exile. They are liberated, global and expansive. As Dambudzo Marechera wrote: "If you write for a particular nation, or tribe, then f*** you." These are the stories of a new Africa, punchy, self-confident and defiant. Final selection includes: Rachida El Charni; Henrietta Rose-Innes; George Makana Clarke; Ivan Vladislavik; Mansoura Ez Eldin; Rogerio Mandjate; Aminatta Forna; Igoni Barrett; Patrice Nganang; Leila Aboulela; Petina Gappah; Ala Al-Aswany; Doreen Baingana; EC Osondu Other writers that may appear include: Olufemi Terry; Abdourahman Waberi; Alain Mabanckou; Veronique Tadjo; Ungulani Ba Ka Khosa; Jean-Luc Raharimanana; Leila Lalami; Milly Jafta; Manuel Rui; Uwem Akpan; Chimamanda Adichie; Zoe Wicombe; Phaswane Mpe; Diane Awerbuck; Ondjaki; Dambudzo Marechera; Camara Laye; Alex La Guma; Brian Chakwava; Ala Al-Aswany; Tahar Ben Jelloum; Yvonne Vera; Monica Arac; Abdulrazak Gurnah; Niq Mhlongo; Fatou Diome; Biyi Bandele; Ben Okri; Tayeb Salih.
The arrangers of marriage / Chimamanda Ngozi Adichie -- Faeries of the Nile / Mansoura Ez-Eldin -- Stickfighting days / Olufemi Terry -- Dancing to the jazz goblin and his rhythm / Brian Chikwava -- Promenade / Henrietta Rose-Innes -- An Ex-mas feast / Uwem Akpan -- Ships in high transit / Binyavanga Wainaina -- The moustached man / Patrice Nganang -- A good soldier / Maaza Mengiste -- Préférence nationale / Fatou Diome -- Homecoming / Laila Lalami -- Street of the house of wonders / Rachida el-Charni -- Bumsters / E. C. Osondu -- Passion / Doreen Baingana -- The fugitive / Alain Mabanckou -- Haywards Heath / Aminatta Forna -- Missing out / Leila Aboulela -- Why don't you carve other animals / Yvonne Vera -- The centre of the world / George Makana Clark -- Propaganda by monuments / Ivan Vladislavić -- Mme Zitta Mendès, a last image / Alaa Al Aswany -- An unexpected death / Ungulani Ba Ka Khosa -- The homecoming / Milly Jafta -- Oxford, black Oxford / Dambudzo Marechera -- You can't get lost in Cape Town / Zoë Wicomb -- Cages / Abdulrazak Gurnah -- The last bordello / Manuel Rui -- The eyes of the statue / Camara Laye -- Slipper satin / Alex La Guma.
First published 2011.
Includes bibliographical references.
Keywords: Africa -- Fiction -- 21st century; Africa -- Social life and customs -- Fiction -- 21st century